MEASURING AND ANALYZING THE IMPACT OF INVESTMENT IN HIGHER EDUCATION ON ECONOMIC GROWTH IN IRAQ FOR THE PERIOD (2004-2023) - Sabah Mahdi Marih (Scholar Express Journals, 2024)
This research sought to identify the nature of the relationship between spending on higher education and economic growth in general. And evaluating the impact of investment in higher education in Iraq through a benchmark study. And an attempt to develop proposals to address the problem of spending on higher education and economic growth in Iraq. The researcher adopted the qualitative-quantitative approach to clarify the causal relationship between the research variables. The problem of the study was based on a hypothesis based on: There is a causal relationship in one direction to the impact relationship of investment in education and its indicators on economic growth in Iraq during the study period from 2004 to 2023. The study reached a set of conclusions, the most important of which is: There is an impact relationship of investment in education on economic growth. The amount of spending on education in relation to total spending varied during the research period. There was a sharp decline in the level of spending during the period (2014-2017), and during this period Iraq experienced unstable security and political conditions, which led to a decrease in total spending
Keywords: investment; education